National archives class C.131 : extents on debt, 1284-1530 - Nightingale, Pamela (UK Data Service, 2004)
This dataset is derived from a research project entitled 'The Economic, Political, and Social Influences on Levels of Credit in Late Medieval England'. The project's primary aim was to create a database which would enable the statistical analyses of medieval credit, and thereby show the principles on which credit worked, and to what degree it was subject to economic, political and social influences; such as high mortality, warfare, taxation and shortages of coin. As a secondary goal, the project sought to explore what records of credit reveal about the changing distribution of wealth and economic activity in England between c. 1280 and 1530.